Kidney Disease and Its Impact on COVID-19 Patients at Sanglah Hospital Denpasar, Bali, Indonesia in 2021 - Upadhana, Putu Satyakumara; Sastrawan, I Gede Gita Sastrawan; Chintya Cahyarini, I Gusti Agung Ayu; Umam, Anbiya Khairul; Putri, Amanda Trisliana Dwi; Adhyatma, I Gede Raka; Somia, I Ketut Agus (Jurnal Penyakit Dalam Indonesia, 2022)
Introduction. Besides having an impact on the respiratory system, COVID-19 also has an impact on other organ such as the kidneys. The systemic inflammatory response thought to be associated with bad prognosis of COVID-19 patients with kidney disease. This study aimed to determine the impact of kidney disease on COVID-19 patients. Methods. This study is an observational analytic study with a cross-sectional approach. The data used is secondary data from the records of confirmed COVID-19 patients who were treated at Sanglah Hospital from 1 May 2021 to 31 August 2021 using total sampling technique.Results. There were 248 patients included in this study. The majority of patients were male (52.4%) with the median overall age of the patients was 59 (range 20–92) years. Most of the patients were severe COVID-19 (65.3%). A total of 77 patients had kidney disease (31.0%) which the most common kidney disease found in patients was acute on chronic kidney disease (n=33; 42.8%). There were significant differences in hemoglobin (p<0.001), blood urea nitrogen (BUN) (p<0,001), serum creatinine (p<0.001), and procalcitonin (p<0.001) in patients classified based on kidney disease. Chi-square analysis showed that COVID-19 patients with kidney disease was correlated with sepsis [PR=2.587 (95%CI 1.750-3.824); p<0.001)], mortality [PR=1.696 (95%CI 1.114-2.583); p=0.018)], and severe COVID-19 [PR=1.513 (95%CI 1.077-2.342); p=0.040)]. Logistic regression analysis showed that COVID-19 patients with kidney disease was correlated with sepsis [PR=4.318 (95%CI 1.767-10.553); p<0,001] and mortality [PR=1.413 (95%CI 1.664-3.005); p=0.045)].Conclusion. Kidney disease increases the risk for sepsis and mortality in COVID-19 patients.